Study protocol: a mixed-methods study to evaluate which health visiting models in England are most promising for mitigating the harms of adverse childhood experiences. Issue 9 (29th September 2022) - Woodman, Jenny; Mc Grath-Lone, Louise; Clery, Amanda; Weatherly, Helen; Jankovic, Dina; Appleton, Jane V; Kirman, Jennifer; Barlow, Jane; Kendall, Sally; Bennett, Samantha; Gilbert, Ruth; Harron, Katie
Abstract : Introduction: Exposure to adverse childhood experiences (ACEs) is associated with poorer health outcomes throughout life. In England, health visiting is a long-standing, nationally implemented service that aims to prevent and mitigate the impact of adversity in early childhood, including for children exposed to ACEs. A range of health visiting service delivery practices exist across England (from the minimum five recommended contacts to tailored intensive interventions), but there is a lack of evidence on who receives what services, how this varies across local authorities (LAs) and the associated outcomes. Methods and analysis: This study will integrate findings from analysis of individual-level, deidentified administrative data related to hospital admissions (Hospital Episode Statistics (HES)) and health visiting contacts (Community Services Data Set (CSDS)), aggregate LA-level data, in-depth case studies in up to six LAs (including interviews with mothers), a national survey of health visiting services, and workshops with stakeholders and experts by experience. We will use an empirical-to-conceptual approach to develop a typology of health visiting service delivery in England, starting with a data-driven classification generated from latent class analysis of CSDS-HES data, which will be refined based on all other available qualitative and quantitative data. We will then evaluate which models of health visiting are most promising for mitigating the impact of ACEs on child and maternal outcomes using CSDS-HES data for a cohort of children born on 1 April 2015 to 31 March 2019. Ethics and dissemination: The University College London Institute of Education Research Ethics Committee approved this study. Results will be submitted for publication in a peer-reviewed journal and summaries will be provided to key stakeholders including the funders, policy-makers, local commissioners and families.